The X-Efficiency of Shariah and Conventional Banking’s in Indonesia - Yumna, Aimatul (Universitas Prasetiya Mulya, 2020)
This paper investigates the X-efficiency of fifteen commercial banks in Indonesia consisting of seven Shariah banks and eight conventional banks. This study uses three stages of data analysis: non-parametric data envelopment analysis (DEA) approach, t-test, and multiple regression method. The results show that in the period of this study, both Shariah and conventional banks in Indonesia have not reached the optimal level of efficiency. However, conventional banks obtain a higher level of allocative and total efficiency compared to Shariah banks. The inefficiency of Islamic banks is stemed from allocative inefficiency rather than technical problems. The bank’s X-efficiency is significantly influenced by size, rather than number of banking channels and staff costs. This study provides important implications for Shariah banking in order to improve X- efficiency and compete in the banking industry in Indonesia by focusing on the improvement of the combination of quality assets.